Marriage of conglomerates and destitute widows: A Narrative Study of Boaz and Ruth Love Story in Book of Ruth Chapters 1-4 - Sugihyono, Sugihyono (Devotion : Journal of Research and Community Service, 2023)
This study aims to conduct a theological study to answer questions, including: why did Boaz want to marry Ruth? Isn't Boaz a wealthy man, famous and of good character? and was not Ruth a poor widow, a cursed Moabite woman (Deuteronomy 23:3)? What was the advantage of the Moabite female Ruth, over the Israelite woman? Are there any values that Boaz held as a prerequisite for him to determine a life partner? In Ruth chapters 2 and 3, it shows that Ruth received preferential treatment from Boaz while picking up barley in her field, Ruth also received a good reception from Boaz when at night she came to her threshing place. This is what the author refers to in discussing and developing this research, especially finding the values that Boaz has to get a wife, as well as knowing the character that Boaz and Ruth have to be a husband and wife who are commensurate with God's will. Using a qualitative approach with a literature study method, through the source of books and literature that correlates with this research problem. From this research it can be concluded that both Boaz and Ruth both had very commendable characters who eventually united them into a commensurate and blessed husband and wife of God. However, above all there was God's involvement and guidance that made the process of Ruth and Boaz's encounter perfect.